Therapeutic potential of mesenchymal stem cells for fungal infections: mechanisms, applications, and challenges - Gao, Yangjie; Ji, Zhe; Zhao, Jingyu; Gu, Julin (Frontiers in Microbiology, 2025)
As a particularly serious condition in immunocompromised patients, fungal infections (FIs) have increasingly become a public health problem worldwide. Mesenchymal stem cells (MSCs), characterized by multilineage differentiation potential and immunomodulatory properties, are considered an emerging strategy for the treatment of FIs. In this study, the therapeutic potential of MSCs for FIs was reviewed, including their roles played by secreting antimicrobial peptides, regulating immune responses, and promoting tissue repair. Meanwhile, the status of research on MSCs in FIs and the controversies were also discussed. However, the application of MSCs still faces numerous challenges, such as the heterogeneity of cell sources, long-term safety, and feasibility of large-scale production. By analyzing the latest study results, this review intends to offer theoretical support for the application of MSCs in FI treatment and further research.